Solve the following quadratic equations by factorisation
Attachments:
![](https://hi-static.z-dn.net/files/d5a/b3051ef7f4e73aa785ccae339d9c998e.png)
Answers
Answered by
1
Step-by-step explanation:
3x^2-√6x-√6x+2=0
√3x(√3x-√2)-√2(√3x-√2)=0
(√3x-2)^2=0
(√3x-√2)(√3x-√2)=0
Answered by
0
Answer:
x=
Step-by-step explanation:
The sum of roots= a+b= (2*6^0.5)/3
The product of roots= a*b= 2/3
By observation, the equation can be written as -
6x^2-(4*x*6^0.5)+4=0
Divide the equation by 6
x^2-(4x/6^0.5)+4/6=0
(x)^2-(2*(2/6^0.5)(x))+(2/6^0.5)^2 which is an expression of (a+b)^2 where a=, b=2/6^0.5
Therefore, (x-2/6^0.5)^2
And the factors are equal to (x-)
Similar questions
Computer Science,
5 months ago
Computer Science,
5 months ago
English,
11 months ago
History,
11 months ago
Science,
1 year ago
Math,
1 year ago
Math,
1 year ago